Challenges of Village Farmers in Facing Globalization (Descriptive Study in Padaherang Village, Padaherang District, Pangandaran Regency) - Cucu Widaty; Fitri Mardiani (Social Studies Conference Proceedings, 2021)
The flow of globalization impacts changes in people's activities, especially in the agricultural sector. This threatens traditional agricultural activities, significantly affecting the lifestyle of the farmers. Therefore, this research aims to find a picture of rural farming communities facing globalization and farmers' responses to globalization. The method in this study is a qualitative descriptive method. The data sources were selected by snowball sampling. The data collection used in the study were observation, interviews, and documentation. The results showed several forms of challenges for farmers in facing globalization, namely competition for farming jobs with other jobs resulting in reduced farmer resources, farmer education is still relatively low, innovation and farmer efficiency are minimal due to imported goods, agricultural society, in general, is still tied to patrons. In addition, clients and the desire for achievement from farmers are low because they still think traditional.